The Use of Gamification for Pre-Recruitment System in Tax Consulting Company - Muthia Maharani; Gunawan Wang (Universitas Bina Darma, 2022)
The increasing need for employees who are experts in the IT field, or commonly referred to as digital talent, is a new challenge for the human resources department in the era of digital transformation. The results of interviews and observations conducted at a tax consulting company show that the HR department does not have a definite procedure for measuring the technical capabilities of IT candidates. Because technology is always changing and evolving, it is difficult to locate someone who is already conversant with the most current technologies and techniques. Assessing a candidate's genuine potential is more difficult than merely reading it on a CV or asking,